Preemptive analgesia effects of Ketamine in patients undergoing surgery. A meta-analysis - Yang,Liqiao (2014)
PURPOSE: To evaluate the preemptive analgesia effects of ketamine for postoperative pain. METHODS: PubMed, EMBASE and Cochrane Library were searched to identify randomized controlled trials (RCTs) involved in ketamine for preemptive analgesic up to March 2013. The relative risk (RR) or mean difference (MD) as well as the confounding 95% confidence interval (CI) were calculated by the Revman 5.0 software. RESULTS: A total of five studies including 266 patients were included in this meta-analysis. Overall, ketamine could reduce the postoperative morphine consumption and significantly prolong the time to first analgesic (p < 0.00001, MD = 0.91, 95% CI: 0.56 to 1.26). However, there was no significant difference in indicators of nausea and vomiting (p = 0.87, RR = 1.04, 95% CI: 0.67 to 1.60), surgical time (p = 0.41, MD = -2.13, 95% CI: -7.21 to 2.95) and anesthetic time (p = 0.53, MD = -1.54, 95% CI: -6.34 to -3.26) between ketamine and control group. CONCLUSIONS: Ketamine was able to accomplish some preemptive analgesic effects of reducing postoperative morphine consumption and prolonging the time to first analgesic. Meanwhile, ketamine was as safe as physiological saline in side effects of nausea and vomiting.